Young Men's Preferences for Design and Delivery of Physical Activity and Nutrition Interventions: A Mixed-Methods Study. (September 2017) - Ashton, Lee M.; Morgan, Philip J.; Hutchesson, Melinda J.; Rollo, Megan E.; Collins, Clare E.
Young adult men are under-represented in health research, and little is known about how to reach and engage them in lifestyle interventions. This mixed-methods study aimed to explore young males' preferences for recruitment strategies, content, format (delivery mode and program duration and frequency), and facilitator characteristics for future physical activity and nutrition interventions. Ten focus groups involving 61 men (aged 18–25 years) in the Hunter region, New South Wales, Australia and an online survey distributed within Australia were completed by 282 males (aged 18–25 years). Key focus group themes included a preference for recruitment via multiple sources, ensuring images and recruiters were relatable; intervention facilitators to be engaging and refrain from discussing negative consequences of being unhealthy. Key program content preferences included skill development and individualized goals and feedback. Focus groups and the survey confirmed a preference for multiple delivery modes, including; face-to-face (group and individual), with support using eHealth technologies. Survey results confirmed the most favored program content as: "healthy eating on a budget, " "quick and easy meals, " and "resistance training." Focus group responses suggested a program duration of ≥6 months, with 2–3 combined face-to-face and supportive eHealth sessions per week. Survey intervention duration preference was 3 months with 4 face-to-face sessions per month. Findings can guide the design, conduct, and evaluation of relevant contemporary physical activity and or nutrition interventions for young men. There is a need to identify the most effective ways to address young men's individual preferences in intervention research.